Utilization Red Tag and One Point Lesson to Optimize Good Housekeeping - Fany Apriliani; Zahriatu Aida (Jurnal Ipteks Terapan (Research Of Applied Science And Education ), 2021)
The existence of Child Welfare Institutions (LKSA) in Indonesia is regulated by the Ministry of Social Affairs and must meet the National Child Care Standards. Within the scope of institutional standards, LKSA must provide complete, adequate, healthy and safe facilities for children to support the implementation of parenting. In general, facilities provided by LKSA can be used together. However, it is still necessary to support children's privacy. Nevertheless, problems that often arise and need special attention are: issues of cleanliness, tidiness, safety and care among fellow foster children. The research objectives are to design red tags and one point lesson to support good housekeeping practices in LKSA. The study object is one of the LKSAs in Bekasi. The methods are: 5S cultural training, observation, designing red tags to manage the sorting of goods and compiling one point lesson with classifications in the form of: safety, basic knowledge, improvement and problem solving. The red tags can be used as a marker for unused items. So that, it is clear to distinguish them from items that are still useful. Furthermore, one-point lesson is expected to be an effective learning medium and easy to practice by personnel in LKSA.